PERMINTAAN TELEPON SELULER PADA PEGAWAI TETAP (STUDI PADA PT. COLOMBUS KENDARI) - Firman, Firman; Saranani, Fajar; Azizah, Nur (JURNAL EKONOMI UHO, 2016)
The aim of research to analyze the determinant of  demand for mobile sellular of  permanent employee  PT. Columbus Kendari  by using statistics  descriptive analysis. The samples used in this study are 65 permanent employees of PT. Columbus Kendari. The variable is measured by using Likert scale (1= strongly disagree; 5= strongly agree). The result showed that the demand for mobile sellular of permanent employee of PT. Columbus Kendari are influenced by the price, income, number of family members, taste  and expectation.  The other side,  taste and  income  are variables that most influence the demand for mobile sellular.